Stylistic changes in the translation process in the interpretation of John Green's The Fault in Our Stars - Xudoyberganova Durdona Ismail qizi (Genius Journals, 2023)
In this article, stylistic change, which is one of the changes that occur in the translation process, is discussed in detail during the analysis of John Green's The Fault in Our Stars. Below are examples of stylistic change to better understand this type of change
Keywords: translator; translation; work; dictionary